Infodemi Di Tengah Pandemi Menurut Perspektif Immanuel Kant - Juliati Elisabeth Seran; Irene Ludji (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
Infodemic in the middle of a pandemic is a crucial problem because the issue has become a phenomenon that morally harms the quality of human life. The amount of information on social media related to COVID-19 includes hoaxes that lead users to wrong thinking and acting. In Indonesia, many negative cases occur due to consuming scams on social media. Seeing the infodemic amid the pandemic, the authors used Immanuel Kant's ethical theory to analyze the phenomenon. Kant's ethics theory emphasizes the role of individuals as moral agents. The results from this analysis show that individuals' inability to play their part as moral agents allows the development of an infodemic in the middle of a pandemic. Apathy in accepting and disseminating information to others without verification is unethical and ultimately influences the quality of the community's life.